A records management policy and file plan for the Versatile Instrumentation System for Science Education and Research (VISSER) project - Rodelas, Hazel Mary R.; Lagrama, Eimee Rhea C. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2015)
It is important for government agencies and organizations, in general, to have a records management system to ensure that records are classified and organized. This study developed a records management policy and file plan for VISSER, a multi-million and multi-disciplinary project funded by the Department of Science and Technology.
The study conducted interviews with the project leader and the staff. Afterwards, the old records management system of VISSER was evaluated. A new records management policy was drafted and after rounds of consultation and pre-trial, the records management policy was finalized.
The conclusions of the study are : 1) Since the old records management system of VISSER proved to be insufficient in organizing and classifying records, therefore a new records management system was designed and formulated to meet the records management needs of the project. 2) There is a need to incorporate much needed inputs to the new records management system, therefore a pre-trial and testing period was conducted. 3) Since VISSER has a simple organizational structure, persons and staff involved can be trained and oriented in a short period of time, therefore all staff concerned were notified and oriented with the new records management system. 4) VISSER accumulated various types of records, therefore these records were classified according to their functions namely administrative, fiscal, legal and research. Records were further arranged by date.
Thesis (Bachelor of Library and Information Science)
Keywords: Records -- Philippines -- Management